Respuestas

2012-07-08T03:57:55+02:00

x + y = 9

X2   +  y2  =53

 

entonces despejamos "x":

x= 9- y

 

X2   +  y2  =53

remplazamos en "x":

(9-y)2     + y2 =53

81 – 18y + y2 + y2 =53

2y2 – 18y + 81 – 53 =0

2y2 – 18y + 28 =0

(2y – 14)(y – 2)= 0

 

entonces: y=2 ; X=9-y , x=9-2=7

17 4 17
2012-07-08T05:20:13+02:00

 x + y = 9 

 

x^2 +y^2 = 53

 

Despejamos x de 

 

x +y = 9 

 

x = 9-y 

 

Sustituimos 

 

(9-y)^2 + y^2 = 53

 

2y^2 -18x + 28 = 0

 

2 (y^2 -9 + 14) = 2 (y-2)(y-7) = 0

 

las soluciones para y  

 

y = 2   ;   y =  7 

 

Sustituimos el valor de y en x = 9-y 

 

x = 9 - 2 = 7 

 

x = 9 -7 = 2 

 

Las soluciones son 

 

x = 7, y = 2  ;   x = 2  , y = 7